IDENTIFICATION OF MEDICINAL COMPOUND IN URIC ACID JAMU BY THIN LAYER CHROMATOGRAPHY METHOD - Muhammad Yani Zamzam; Iin Indawati; Nina Karlina; Elsa Tiakomala; Windah Widia Ningrum; Aulia Nurkahfi; Andriana (Medical Sains : Jurnal Ilmiah Kefarmasian, 2023)
Jamu is one of the traditional medicines derived from natural ingredients distributing in Indonesia. In accordance with Permenkes No. 007 of 2012, Medicinal Compound (MC) are prohibited from being added to jamu products. Previous research has found that some of the products in public contain MC. The aim of this study is to determine the presence or absence of allopurinol, piroxicam, and dexamethasone in uric acid jamu.  This research used 5 (five) samples of uric acid jamu, both those with and without distribution permits from The Indonesian Food and Drug Authority, randomly selected in Kedawung District, Cirebon Regency, West java, Indonesia. The identification method used in this study is Thin Layer Chromatography (TLC) with the stationary phase being silica gel GF 254. For the identification of allopurinol, the mobile phase is n-butanol: ammonium hydroxide: ethanol; for piroxicam identification, it is ethyl acetate-methanol-ammonia (6:3:1); and for dexamethasone identification, it is chloroform: acetone (1:4). Spot detection is done using ultraviolet (UV) light at 254 nm. The applied solutions are the test solution (A), the test solution with added allopurinol, piroxicam, or dexamethasone (B), and the reference standard solution (C). The research results from the 5 (five) samples of uric acid jamu identified one positive samples containing allopurinol, and all positive samples contained piroxicam and dexamethasone. Keywords: Jamu,  thin-layer chromatography, allopurinol, piroxicam, dexamethasone